The mineral-water interface: Where minerals react with the environment - Putnis, Christine; Ruiz-Agudo, E. (2013)
The reactions that occur at the mineral–water interface are central to all geochemical processes. They affect a wide range of important Earth processes, all of which involve geochemical element cycling. Examples include weathering and soil formation, nutrient availability, biomineralization, acid mine drainage, the fate of contaminants, nuclear waste disposal, and minor element incorporation and partitioning during mineral growth. Each of these processes, and its reaction rates, is ultimately controlled by reactions that occur at mineral surfaces. Through the development of advanced analytical methods, direct observations of mineral reactions at the nanoscale have enabled exciting new possibilities for clarifying the mechanisms governing mineral–fluid reactions.